Analysis of Genetic Diversity and Population Structure in Three Forest Musk Deer Captive Populations with Different Origins. Issue 4 (1st April 2019) - Fan, Jiamin; Zheng, Xueli; Wang, Hongyong; Qi, Hong; Jiang, Benmo; Qiao, Meiping; Zhou, Jianwen; Bu, Shuhai
Abstract: Musk deer (Moschidae), whose secretion is an expensive and irreplaceable component of traditional medicine, have become endangered in the wild due to habitat fragmentation and over-exploitation. In recent years, China has had success in the artificial breeding of forest musk deer, thus relieving the pressure on wild populations. However, many farmed populations are experiencing degradation, and little genetic information is available for conservation management. In this study, we selected 274 individuals from three typical captive populations (originated from the Ta-pa Mountains (Tp), the midrange of the Qinling Mountains (Ql) and the Western Sichuan Plateau (WS), respectively) to evaluate the genetic variations. A total of more than 3.15 billion high-quality clean reads and 4.37 million high-quality SNPs were generated by RAD sequencing. Based on the analysis, we found that captive forest musk deer populations exhibit a relatively low level of genetic diversity. Ql displayed a higher level of genetic diversity than the Tp and WS populations. Tp and WS had experienced population bottlenecks in the past as inferred from the values of Tajima's D. There were high levels of heterozygote deficiency caused by inbreeding within the three populations. Population structure analysis suggested that the three populations have evolved independently, and a moderate amount of genetic differentiation has developed, although there was a low level of gene flow between the Ql and Tp populations. Furthermore, the average quantities of musk secreted by musk deer in the Tp and WS populations were significantly higher than that in the Ql population. The present genetic information should be considered in management plans for the conservation and utilization of musk deer from captive breeding.